Modeling, simulation and optimization of complex processes HPSC 2015 : Proceedings of the Sixth International Conference on High Performance Scientific Computing, March 16-20, 2015, Hanoi, Vietnam /: Proceedings of the Sixth International Conference on High Performance Scientific Computing, March 16-20, 2015, Hanoi, Vietnam. (2017) - Unknown
No abstract available